2017
DOI: 10.1080/17453674.2017.1307032
|View full text |Cite
|
Sign up to set email alerts
|

Revision after shoulder replacement for acute fracture of the proximal humerus

Abstract: Background and purposeFor more than half a century, stemmed hemiarthroplasty (SHA) has been used in the treatment of comminuted and displaced fractures of the proximal humerus. Reverse shoulder arthroplasty (RSA) has been increasingly popular in cases where it is difficult to obtain satisfactory fixation of the tuberosities. We report revision rates and reasons for revision after shoulder arthroplasty for acute fractures of the proximal humerus.Patients and methodsThis study was based on a common dataset from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 13 publications
1
26
1
1
Order By: Relevance
“…The proportion of revisions in our study corresponds with the 3% reported by both the NARA group (Brorson et al. 2017) and in a study of 422 Norwegian patients undergoing SHA for acute proximal humeral fractures (Fevang et al. 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of revisions in our study corresponds with the 3% reported by both the NARA group (Brorson et al. 2017) and in a study of 422 Norwegian patients undergoing SHA for acute proximal humeral fractures (Fevang et al. 2009).…”
Section: Discussionsupporting
confidence: 89%
“…2013, Brorson et al. 2017). However, revision rates do not necessarily reflect the functional outcome as some arthroplasties are never revised due to patient- or surgery-related factors.…”
mentioning
confidence: 99%
“…We found that the 12-year cumulative survival rate after PHFS was 85% for SHA and 86% for RSA. This is clearly lower than survival rates found for acute PHF (Brorson et al 2017). A plausible explanation may be that it is more difficult, with more surgical trauma added, to insert an arthroplasty when the indication is PHFS relative to acute PHF.…”
Section: Discussionmentioning
confidence: 77%
“…However, a revision after failed RSA can be more challenging than after hemiarthroplasty and some surgeons may hesitate to revise an RSA despite a poor functional outcome. This would lead to an underestimation of failures of RSA overall and relative to hemiarthroplasty (Namdari et al 2013, Brorson et al 2017. There may be different indications for both primary and revision arthroplasty not only among countries but also among regions, hospitals, surgeons, and maybe also for the same surgeon from time to time.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, conventional HA, i.e., SHA (Fig. 1a), is commonly performed but has some disadvantages, such as erosion of the native glenoid, loss of joint space and posterior humeral subluxation, which contribute to poor satisfaction and high revision rates in many cases, especially in young population [27][28][29]. To reduce the aforementioned potential risks, the Copeland Mark 3 resurfacing arthroplasty was, for the first time, introduced in 1993 as the first-generation RHA (Fig.…”
Section: Introductionmentioning
confidence: 99%